A comparison between the precipitation and impregnation methods for water-gas shift catalysts - Pereira, Amalia Luz C. (2007)
The precipitation and impregnation methods in the preparation of chromium-doped magnetite for water gas shift reaction (WGSR) were compared in this work. This reaction is an important step in the commercial production of highly pure hydrogen from natural gas or naphtha feedstocks. It was found that the preparation method affects both the textural and catalytic properties of chromium-doped magnetite. However, chromium was able to preserve the specific surface area during the WGSR and to delay the metallic iron production, independently of the preparation method. Chromium caused a decrease in activity per area, depending on the preparation method. This fact was assigned to its ability in making the production of Fe2+ species more difficult, making the catalytic sites less active, because the redox cycle of the reaction becomes more difficult. The most active catalyst was obtained by adding chromium by impregnation, which led to a large amount of total chromium in the solid and then a catalyst with high specific surface area was produced. It was showed that the catalysts can be prepared in the active phase avoiding the reduction step, before reaction